What 5,000 acknowledgements tell us about informal collaboration in financial economics - Michael E. Rose; Co-Pierre Georg (Kiel Institute for the World Economy (IfW), 2021)
We present and discuss a novel dataset on informal collaboration in financial economics, manually collected from more than 5,000 acknowledgement sections of published papers. We find that informal collaboration is the norm in financial economics, while generational differences in informal collaboration exist and reciprocity among collaborators prevails. Female researchers appear less often in acknowledgements than comparable male researchers. Information derived from networks of informal collaboration allows us to predict academic impact of both researchers and papers even better than information from co-author networks. Finally, we study the characteristics of the networks using various measures from network theory and characterize what determines a researcher's position in it. The data presented here may help other researchers to shed light on an under-explored topic.
Keywords: A14; D83; G00; O33; 330; intellectual collaboration; acknowledgements; social networks; financial economics